Pelaksanaan Self Monitoring of Blood Glucose pada Pasien DM Tipe 2 di Kota Blitar: Bahasa Indonesia - Sepdianto, Tri Cahyo (Jurnal Keperawatan Malang, 2019)
Self Monitoring of Blood Glucose is an examination of blood sugar carried out by patient themselves. The purpose of this study is to decribe the implementation of the Self Monitoring of Blood Glucose. The study design with a sample of 30 people. Questionnaire and observation are used for data collection. The result showed that patients who performed Self Monitoring of Blood Glucose were 50% (15 patients) (n=30) had a blood sugar profile in the normal range when fasting blood sugar was 53% (8 patients) and 2 haours post prandial were 73% (11 patients) with a place of execution at home and health services as much as 47% (14 patients). The purpose of this Carlsen study is to help patient to control their blood sugar profile.